2007
DOI: 10.1111/j.1551-2916.2007.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of SrFeO3‐Based Materials in H2O/CO2‐Containing Atmospheres at High Temperatures and Pressures

Abstract: The chemical stability of SrFeO3‐based perovskites in H2O‐ and CO2‐containing atmospheres at high temperatures and pressures has been examined. The extent of reaction as a function of pCO2, pH2O, temperature, and time has been determined. Either strontium carbonate or Sr(OH)2·H2O was observed on sample surfaces after exposure. Observation of two different reaction‐rate behaviors could be explained by the formation of different products. The stability of the perovskite has been found to increase when the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…A formation of carbonates could not been detected [11,12]. Further publications discuss the influence of humidified atmospheres with different material compositions comparable to the BSCF-material [13][14][15][16]. In the field of oxygen sensors and cathode materials for fuel cells the impact of CO 2 has been studied as well [17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…A formation of carbonates could not been detected [11,12]. Further publications discuss the influence of humidified atmospheres with different material compositions comparable to the BSCF-material [13][14][15][16]. In the field of oxygen sensors and cathode materials for fuel cells the impact of CO 2 has been studied as well [17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have suggested that the hydrogen formed during the reaction can interact with oxygen species on the membrane surface to form water [2]. In addition, it has been suggested that CO 2 and CO can form carbonate species on the membrane surface [18,19]. The formation of H 2 O and the adsorption and potential reaction of CO and CO 2 on the membrane surface can significantly change the product composition and the overall reaction scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Stability of this material in humid atmospheres in the presence of CO 2 is presented in a separate paper. 13 …”
Section: Introductionmentioning
confidence: 97%